I Feel Fall Weather - Mari Schuh
What is fall weather like where you live? Is it cold or windy? Does it rain a lot? This book helps students observe and examine the world around them as the season changes from summer to fall. Engaging and informative, with clear imagery and captions, students learn to identify and describe contrasting aspects of fall weather.